The Effects of Intellectual Capital on Firms’ Sustainable Growth: A Systematic Review and Future Research Agenda - Suong, Pham Thi Ngoc; Vo, Dut Van (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 4, 2022)
This study aims to review the effects of intellectual capital on enterprises' sustainable growth and proposes a research agenda to the literature. Seven relevant studies published in journals indexed in the Web of Science and Scopus were selected and reviewed by systematically searching the relevant database. The study applied the co-occurrence technique by the VOSviewer application to detect the limitations of prior studies. Review results reveal that intellectual capital is measured by many different methods and comprises many components. Most empirical studies concluded the positive effect of enterprises’ intellectual capital on sustainable growth. However, others only find out the general effect of intellectual capital on sustainable growth or the effect of some components of intellectual capital on sustainable growth. Building upon such research gaps, the study proposes a model for such a relationship and the moderating role of the management experience of the top management team on the association to improve the robustness of future studies in the field.